The polymorphisms of MIR31HG gene is correlated with alcohol-induced osteonecrosis of the femoral head in Chinese Han male population - Liu, Wei; Wang, Xin; Chen, JianFei; Zeng, Fan; Xiong, Jun (Frontiers in Endocrinology, 2022)
Background: Alcoholic osteonecrosis of the femoral head (ONFH) is a multifaceted illness that seriously disturbs the patients’ quality of life. The role of lncRNAs in alcoholic ONFH has attracted widespread attention in recent years. This study mainly explored whether MIR31HG polymorphism affects the risk of ONFH. Methods: There were 733 males (308 alcohol-induced ONFH patients and 425 healthy controls). Seven single nucleotide polymorphisms from MIR31HG were genotyped using the Agena MassARRAY platform. Odds ratio (OR) and 95% confidence intervals (CI) via logistic regression was applied to assess the contribution of MIR31HG variants to alcoholic ONFH susceptibility. Results: We found that rs10965059 was related to a lower risk of alcoholic ONFH in the overall, age, and necrotic sites analysis. Rs10965064 also showed a risk-reducing effect in the occurrence of alcoholic ONFH patients older than 40 years old. Conclusions: We confirmed that MIR31HG variants have a significant correlation with the occurrence of alcoholic ONFH among the Chinese Han male population. our findings may provide new ideas for understanding the effect of MIR31HG on the prevention and diagnosis of alcoholic ONFH.